The Armory Show 2010. - De Backer, Katelijne; Piers 92 and 94, New York City; The Armory Show New York City 2010 ([s.l.] : [s.n.], 2010)
Collins, Susan ; Calder, Alexander ; Ernst, Max ; Giacometti, Alberto ; Kandinsky, Wassily ; Magritte, René ; Matisse, Henri ; Miro, Joan ; Picasso, Pablo ; Le Corbusier ; et al.
The Armory Show 2010, Piers 92 and 94, New York City, 4.03 - 7.03.2010
kunstcatalogus